Pandemic Documents: The Case of Mobility Permits During Lockdown in Chile - Araya-Moreno, Javiera (Anthropologica, 2022)
I reflect on how the COVID-19 pandemic in Chile became a question of bureaucratic knowledge and official documents. Through the analysis of COVID-19 permits, the tool implemented by the Chilean government in order to manage mobility in zones under lockdown, I focus on two features of documents: their denotational properties and their performative marginality. I argue that COVID-19 permits in Chile functioned as an “anti-document.” While they did not establish stable and meaningful connections with individuals’ daily lives, they produced a series of considerable effects on them, the most tangible of these effects probably being the detention and criminal prosecution of individuals caught on the street without the appropriate permit. In contrast with how documents participate in socio-legal configurations – being a means to an end – COVID-19 permits were central to the implementation of the confinement policy.